PERANAN ORGANISASI ROHANI ISLAM DALAM MENINGKATKAN NILAI RELIGIUS DAN KEJUJURAN SISWA - Desi Narita; Irawan Suntoro; Hermi Yanzi (Jurnal Kultur Demokrasi, 2016)
The purpose of this research was to describe various activities of Islamic spiritual organization (Rohis) that play a role in increasing the value of religious and rectitude students. The research methodology used in this research descriptive qualitative with the informants were vice headmaster of student field, the trustees of Islamic spiritual organization, former trustees of Islamic spiritual organization and member of Islamic spiritual organization. Technique of data collection used was interview guidelines, observation guidelines, documentation guidelines and likert scale. Technique data analysis was using analysis of interactive model. Based on the result of the research which has been done, it is known that Islamic spiritual activities in proselytizing common (study Islamic basic, guidance in reading Al-Quran, tadabur of nature, wall magazine), have a role in increasing the value of religious while the activities in special proselytizing (mentoring) have a role in increasing value of rectitude students in Senior High School 1 Pesisir Barat.Tujuan penelitian ini adalah mendekripsikan peranan kegiatan organisasi Rohani Islam (Rohis) yang berperan dalam meningkatkan nilai religius dan kejujuran siswa. Metode penelitian yang digunakan dalam penelitian ini deskriptif kualitatif dengan informan wakil kepala sekolah bidang kesiswaan, pembina Rohani Islam, mantan pembina Rohani Islam, dan anggota Rohis. Teknik pengumpulan data menggunakan pedoman wawancara, pedoman observasi, pedoman dokumentasi dan skala likert. Teknik analisis data menggunakan Analysis Interactive Model. Berdasarkan hasil penelitian yang telah dilakukan dapat diketahui bahwa kegiatan Rohani Islam dalam dakwah umum (studi dasar Islam, bimbingan baca Al-Quran, tadabur alam, majalah dinding) berperan dalam meningkatkan nilai religius sedangkan kegiatan dalam dakwah khusus (mentoring) berperan dalam meningkatakan nilai kejujuran siswa di SMA Negeri 1 Pesisir Barat.Kata kunci: dakwah khusus, dakwah umum, nilai kejujuran, nilai religius, rohani Islam